2003
DOI: 10.1159/000074535
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Trace Proteinuria

Abstract: Background: The clinical significance of a trace protein reading on urinalysis is unclear, and such a result is often ignored by the clinician. Methods: We examined 185 samples of urine with trace proteinuria by both Chemstrips and sulfosalicylic acid testing, and compared the results with those of urinary albumin and total protein concentrations. Results: Taking for the purposes of this study an arbitrary upper limit of normal of 20 mg/l for albumin and 100 mg/l for total protein concentration, we found abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…In this study, we found that the proportion of individuals with positive albuminuria was significantly greater ( p < 0.0001) in Group 2 than Group 1. This result indicates that trace proteinuria levels could be a useful indicator of albuminuria in patients with diabetes mellitus, and this has also been previously reported (Sam et al 2003). However, the sensitivity and the specificity of the urine dipstick test are not always sufficient to detect microalbuminuria.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we found that the proportion of individuals with positive albuminuria was significantly greater ( p < 0.0001) in Group 2 than Group 1. This result indicates that trace proteinuria levels could be a useful indicator of albuminuria in patients with diabetes mellitus, and this has also been previously reported (Sam et al 2003). However, the sensitivity and the specificity of the urine dipstick test are not always sufficient to detect microalbuminuria.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, a survey undertaken in Okinawa after 17 years of follow-up indicates that individuals with dipstick-positive proteinuria are at increased risk of developing CKD, in fact in proportion to the severity of proteinuria [28]. Sam et al [29] have demonstrated that trace dipstick proteinuria usually means microalbuminuria. Indeed, in their survey, a negative urinalysis for proteinuria excluded microalbuminuria in 87% and proteinuria in 78% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A related issue is that determination of proteinuria was based on a single random dipstick urinalysis rather than repeated quantitative measures such as urinary albumin to creatinine ratio. Because we did not have information on microalbuminuria, we used trace (rather than 1ϩ) proteinuria to define CKD in patients with mildly reduced GFR, recognizing that this probably increased sensitivity for earlier forms of diabetic nephropathy while reducing specificity for other types of CKD (35,36). For these reasons, some patients may have been misclassified with respect to CKD status.…”
Section: Discussionmentioning
confidence: 99%